Multiple-Modal-Coupling Modeling and Stability Analysis of Cold Rolling Mill Vibration - Lingqiang Zeng; Yong Zang; Zhiying Gao (Shock and Vibration)
An effective dynamic model is the basis for studying rolling mill vibration. Through analyzing characteristics of different types of vibration, a coupling vibration structure model is established, in which vertical vibration, horizontal vibration, and torsional vibration can be well indicated. In addition, based on the Bland-Ford-Hill rolling force model, a dynamic rolling process model is formulated. On this basis, the rolling mill vertical-torsional-horizontal coupled dynamic model is constructed by coupling the rolling process model and the mill structure model. According to this mathematical model, the critical rolling speed is determined and the accuracy of calculated results is verified by experimental data. Then, the interactions between different subsystems are demonstrated by dynamic responses in both time and frequency domains. Finally, the influences of process parameters and structure parameters on system stability are analyzed. And a series of experiments are conducted to verify the correctness of these analysis conclusions. The results show that the vertical-torsional-horizontal coupled model can reasonably characterize the coupling relationship between the mill structure and the rolling process. These studies are helpful for formulating a reasonable technological procedure of the rolling process and determining a feasible dynamic modification strategy of the structure as well.